The Profile of Brain Tumor Cases in RSUD Dr Soetomo, Surabaya - R. Yuvasanghar Ravindra Mohan; Joni Wahyuhadi; Ni Wajan Tirthaningsih (Humanistic Network for Science and Technology (HNST), 2021)
Brain tumor is a condition affecting many people worldwide.Patients often had similar functional neurological symptoms even if the type of tumors diagnosed were entirely different at a later stage.Some of the neurological symptoms were tingling in the feet, changes in eyesight,tremors in the extremities, headaches or migraines and more. Patients who suffer from brain tumor go through a screening process to identify the cause of the problem. Factors such as age and gender was observed in this study which affected the data distribution of brain tumors. This study aimed to find the data distribution of the brain tumor cases in RSUD Dr Soetomo. The results obtained showed that the highest number of brain tumor found were meningiomas followed by unspecified brain neoplasms as the second highest and adenomas being the third highest tumor type found in RSUD Dr Soetomo. The total number of female patients with brain tumor were higher than that of males. The median age of the patients was found to be 45. The highest number of tumor cases were seen in the adult age group followed by teens, children and elderly. The benign tumor type is found to be higher in number as compared to malignant. The number of supratentorial tumors are also found to be higher than infratentorial overall. Keywords: age; gender; brain tumor